Programa Nacional para a Promoção da Atividade Física - Shinn, Cecília (2020)
Primary health care, due to its proximity and easy access, knowledge of the family and their community, and through preventive measures and continuity of care, has an important and decisive role to play in counselling and promotion of physical activity throughout the various stages of life. Portugal has the lowest levels of physical activity in Europe and high levels of sedentary lifestyle, which led the Directorate General of Health to establish Physical Activity as a priority health programme, and develop the National Strategy for Promotion of Physical Activity. This article aims to describe initiatives that have been implemented that promote physical activity. More family physicians have become interested in promoting physical activity in their clinical practice. Specific training has become more widely available, computer based tools have been developed as clinical practice aids (for evaluation of levels of physical activity and counselling) and local initiatives involving health professionals have increased, as well as more investment in terms of investigation and monitoring of all of the above. At the same time change is happening among urban spaces and local policies that favour physical activity.